A Reservoir of Voices: Franco-Ontarien Folksongs - Laxer, Daniel (Ontario History, 2009)
French Canadian folksong collections are complex sources of oral history. They contribute a valuable perspective to the limited documentation of the lumbering and fur trade eras. Similar to Ernest Gagnon’s seminal Chansons populaires du Canada, Germain Lemieux’s collections of Franco-Ontarien folksongs are presented alongside a nationalist agenda. Yet Lemieux improves upon Gagnon’s methodologies and analysis, adopting the fieldwork techniques and historical approach established by Marius Barbeau. Lemieux’s collection ultimately reveals much about the midtwentieth century Franco-Ontarien struggle for survivance. Most importantly, it preserves the fragmented voices of coureurs de bois and voyageurs, men who sang and composed amongst the diverse peoples of the North American fur trade.